KUALITAS SUSU BERBAHAN DASAR BIJI LAMUN JENIS Enhalus acoroides: Penentuan Nilai Viskositas dan Pengujian Sifat Mikrobiologi di Laboratorium - Yulviany Latuihamallo; Theopilus Watuguly; Prelly M.J Tuapattinaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2019)
Background: Seagrass is a group of closed seed plants (Angiosperms) and single-sided (monocotyledonous) plants which are able to live permanently below sea level. One of the most abundant types of seagrass in Indonesian waters is seagrass Enhalus acroides. The specialty of seagrasses Enhalus acoroides is that the seeds can be used as food ingredients in several regions. Some people in Maluku process seagrass seeds into vegetables for daily use. In addition, seagrass seeds Enhalus acoroides which have good nutrition can be processed into milk products that can be an alternative to animal milk. Methods: The viscosity test for seagrass seed milk using the Ostwald method and microbiological analysis through the plate count total test using the SNI 2008 guidelines. This research was located in the Basic Biology Laboratory, Faculty Teacher Training and Education, Pattimura University and the Industrial Research and Standardization Center Laboratory in Ambon. Results: Viscosity values ​​in seagrass seed milk in the treatment group S0 (without sugar) 121.69 cP, treatment S1 (100 grams of sugar) 160.76 cP and treatment of S2 (200 grams of sugar) 156.38 cP while the results of the Total Plate Count test in seagrass seed milk with treatment S0 (no sugar) 7.1x101, treatment S1 (100 grams of sugar) 6.0x101 and treatment S2 (200 grams of sugar) 7.0x101. Conclusion: The highest viscosity value is in the treatment of S1 (100 grams of sugar) 160.76 cP and the lowest viscosity value is in the treatment of S0 (without sugar) 121.69 cP while the highest microbial colonies are in treatment S0 (without sugar) 7,1x101 and the lowest microbial colonies were in treatment S1 (100 grams of sugar) 6.0x101.